Cognitive And Affective Customer Experiences: Antecedent Of Customer Satisfaction - Parawansa, Dian Anggraece Sigit; Abadi, Rahmat Riwayat; Aslam, Annisa Paramaswary (CV. AFDIFAL MAJU BERKAH, 2023)
The occurrence of the internet in accessing information has changed the way people view shopping activities. Currently, shopping can be done anywhere and anytime without having to do mobility due to the available mobile apps. This study aims to analyze how much influence cognitive customer experiences and affective customer experiences have on customer satisfaction in Fore Coffee consumers who use mobile apps. Methods of data collection using interviews and questionnaires using a Likert scale and determining the sample in this study were 100 respondents using nonprobability sampling technique with purposive sampling method. To analyze the data in this study, multiple linear regression analysis was used with the help of SPSS version 25 software. The findings show that cognitive customer experiences have a significant effect on customer satisfaction, affective customer experiences have a significant effect on customer satisfaction, and cognitive customer experiences and affective customer experiences have a significant effect on customer satisfaction.